Review paperClinical significance of vehicles in topical corticosteroids - Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Recently in order to reduce costs of treatment both from the national budget and for patients there has been a worldwide tendency to promote new generic formulations. Because these formulations are usually introduced to the market a couple of years after the original medications in the case of topical ones the characteristics of their bases may be different. This article presents differences in the composition of bases of selected topical corticosteroids containing mometasone furoate: Elocom ® – original medication (Schering Plough) and Elosone ® – generic medication (Blau Farma) as well as clobetasole propionate: Dermovate ® – original medication (GlaxoSmithKline) and Novate ® – generic medication (Blau Farma). Results of the investigation performed in a population of dermatologists revealed a good opinion and significance of arguments presented in the promotion materials prepared for the Blau Farma modern bases of topical corticosteroids. When making a decision about administration of any generic medication we should have knowledge of their efficacy and safety.